2002
DOI: 10.1086/339969
|View full text |Cite
|
Sign up to set email alerts
|

On the Recent History of Star Formation in the Blue Compact Dwarf Galaxy VII Z[CLC]w[/CLC] 403

Abstract: Here we attempt to infer the recent history of star formation in the BCD galaxy VII Zw 403, based on an analysis that accounts for the dynamics of the remnant generated either by an instantaneous burst or by a continuous star formation event. The models are restricted by the size of the diffuse X-ray-emitting region, the H luminosity from the star-forming region, and the superbubble diffuse X-ray luminosity. We have reobserved VII Zw 403 with a better sensitivity corresponding to the threshold H flux 8:15 Â 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
2
26
1
Order By: Relevance
“…We corrected the data from Martin (1998) in the same way; the luminosity is given for a distance of 4.5 kpc. Silich et al (2002) applied a correction only for the background extinction E(B − V ) = 0.02, as inferred by Burstein and Heiles (1984); the correction for internal extinction in VII Zw 403 increases further the flux and luminosity found by these authors. As follows from Table 3, our measured Hα luminosity of the galaxy is considerably lower than the value obtained by Silich et al (2002) and agrees well with the previous estimates by Lynds et al (1998) and Martin (1998).…”
Section: The [Sii]/(hα+[nii]mentioning
confidence: 88%
See 2 more Smart Citations
“…We corrected the data from Martin (1998) in the same way; the luminosity is given for a distance of 4.5 kpc. Silich et al (2002) applied a correction only for the background extinction E(B − V ) = 0.02, as inferred by Burstein and Heiles (1984); the correction for internal extinction in VII Zw 403 increases further the flux and luminosity found by these authors. As follows from Table 3, our measured Hα luminosity of the galaxy is considerably lower than the value obtained by Silich et al (2002) and agrees well with the previous estimates by Lynds et al (1998) and Martin (1998).…”
Section: The [Sii]/(hα+[nii]mentioning
confidence: 88%
“…Based on HST observations, Lynds et al (1998) identified a shell structure of several bright HII regions 70-150 pc in size. Silich et al (2002) found traces of the faint giant (D ≃ 500 pc) ring in the Hα emission from the diffuse gas. An extended region of diffuse X-ray emission inside the giant ring was reported, but these data have not yet been confirmed (Papaderos et al 1994;Lira et al 2000;Bomans 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lynds et al [2] used slit spectrograms obtained on the 4-m telescope of the Kitt Peak National Observatory to derive the shells expansion rate, 50−70 km s −1 , although these results were not confirmed by Lozinskaya et al [1] (see below). Silich et al [7] found traces of a giant (D ≃ 500 pc), faint ring in Hα emission produced by diffuse gas. Reports of the presence of an extended region of diffuse X-ray emission inside this giant ring remain, for the moment, unconfirmed [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The HST observations have disclosed a shell-like structure of several bright HII regions; Lynds et al [5] measured the shell's expansion velocity of 50 − 70 km/s, however, Lozinskaya et al [4] did not confirm these results. Silich et al [13] found the traces of a faint giant ring sized D ≃ 500 pc in the H α emission of diffuse gas.…”
mentioning
confidence: 99%